CREATING A STRATEGICALLY-ORIENTED SYSTEMMANAGEMENT OF ENTREPRENEURAL STRUCTURESIN THE FIELD OF SERVICES - TAYLAKOVA DILAFRUZ BAYMAMATOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The first decade of the21stcentury ischaracterized by theactivedevelopment of theservice sector in most countries of the world: the number of service organizations is increasing, the number of people employed in thisfield is increasing, and the range of services offered is expanding.The development trend of the service sector isalsoobservedinmodern Russia: thenumber and nomenclature of the corresponding organizations are expanding rapidly, the number of employees employed in theservice isgrowing.However, developmentdomestic service sector occurs spontaneously without clear strategic guidelines, since under the influence of market processes, almost all organizations of the national economy begin to perform service functions not inherent to them.In theseconditions, there is a need to study the features of strategic management processes in the paid services sector and to create, on their basis, scientifically-based strategic management techniques for its constituent entities.Problems of functioning of the sphereinservants andorganizations of the sphere of us the meadow is covered in domestic and foreign literature in sufficient detail.Meanwhile, there are practically no studies aimed at improving the competitiveness ofbusiness structuresoperating in this sector of the economy.Consideration of the features of entrepreneurial activity in the service sector is episodic in nature, being, as a rule, only oneof a widerange of covered aspects.In this regard, a study focused onidentifying the featuresof strategic management processes in business structures of the service sector is relevant and timely, since it allows you to determine the prospects for the development of business in this area